How would you remove these temporal-zygomatic lesions? Surgical reconstruction of the temporal-zygomatic area using a mandibular Burow's triangle advancement flap - Laura Miccio; Fortunato Cassalia (PAGEPress Publications, 2024)
A 65-year-old man was referred with two adjacent skin lesions located in the right temporal and zygomatic area. Dermoscopic examination revealed features indicative of two basal cell carcinomas, prompting the scheduling of surgical removal. [...]